Secondary battery and electric device
Patent Information
- Application Number
- CN202480001336.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-10
- Filing Date
- 2024-06-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-07
AI Technical Summary
It is difficult to further improve the mass energy density of existing lithium-ion batteries. They are limited by the theoretical capacities of positive and negative electrode materials and cannot meet the market's demand for high energy density.
The combination of cathode active material with high nickel content and carbon-silicon composite material is used. The carbon-silicon composite material includes a carbon skeleton with a three-dimensional network cross-linking and silicon nanoparticles attached to it. By optimizing the carbon and silicon elements of the carbon-silicon composite material distribution, improving the energy density and cycle performance of secondary batteries.
The simultaneous optimization of high energy density and cycle performance of secondary batteries is achieved, significantly increasing the mass energy density of the battery while improving cycle stability and rate performance.
Smart Images

Figure CN119137766A_ABST
Abstract
Description
Secondary batteries and electrical devices
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to patent application number PCT / CN2023 / 087384, filed on April 10, 2023, and entitled “Secondary Batteries and Electrical Devices,” the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present application relates to the technical field of lithium batteries, and in particular to a high-energy-density secondary battery and an electrical device. Background Art
[0004] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's performance requirements for secondary batteries have become increasingly higher.
[0005] Lithium-ion batteries are currently widely used small secondary batteries with high quality and high energy density, but with the rapid development of their application fields, there is an urgent need to further improve their energy density.
[0006] Summary of the Invention
[0007] The present application has been made in view of the above-mentioned problems, and an object of the present application is to provide a secondary battery having a high energy density.
[0008] In a first aspect of the present application, a secondary battery is provided, comprising: a positive electrode plate, the positive electrode plate comprising a positive electrode film layer, the positive electrode film layer comprising a positive electrode active material comprising a transition metal element, the molar content of nickel being not less than 85% based on the total molar number of the transition metal element in the positive electrode active material, and the energy per unit area of the positive electrode film layer on a single side of the positive electrode plate being 15-35 mWh / cm 2 , optional 20-35mWh / cm 2 ;
[0009] A negative electrode plate comprises a negative electrode film layer, wherein the negative electrode film layer comprises a negative electrode active material of a carbon-silicon composite material, wherein the carbon-silicon composite material comprises carbon matrix particles having a carbon skeleton and silicon nanoparticles attached to the carbon skeleton.
[0010] The present application breaks through the limitation of the theoretical capacity of positive and negative electrode materials in the prior art by combining a positive electrode active material with a high nickel content with a carbon-silicon composite material, and realizes the preparation of a secondary battery with a high energy density.
[0011] In any embodiment, the shell weight z of the secondary battery and the bare cell weight JR of the secondary battery satisfy the following relationship: 0.01≤z / JR≤0.42; optionally 0.01≤z / JR≤0.1 or 0.02≤z / JR≤0.07.
[0012] Through the above structural design, the mass of the secondary battery is further reduced and the energy density of the battery is significantly improved.
[0013] In any embodiment, the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon nanoparticles are disposed in the three-dimensional network cross-linked pore structure.
[0014] Although silicon nanoparticles have a large theoretical gram capacity, they expand significantly during charge and discharge, resulting in poor structural stability and deteriorating battery cycle performance. The carbon-based particles in this application possess a stable, three-dimensional, cross-linked porous skeleton structure, which provides ample space for the silicon nanoparticles, making them less likely to agglomerate while mitigating the adverse effects of their volume expansion on the negative electrode, thereby effectively improving the cycle performance of secondary batteries.
[0015] A high nickel content can increase the gram capacity of the positive electrode, thereby increasing the energy density of the secondary battery. However, an excessively high nickel content can increase the lithium-nickel mixing phenomenon, making it easier for transition metals to dissolve and deposit on the negative electrode, affecting the battery's cycle performance. The three-dimensional cross-linked carbon skeleton of the carbon-silicon material of the present application can form a complex with the positive electrode active material, reducing the deposition of transition metals on silicon nanoparticles and reducing the negative impact of transition metal deposition on the negative electrode on the performance of silicon-based materials, thereby further improving the cycle performance of the secondary battery.
[0016] In any embodiment, in the peripheral region of the carbon-silicon composite material, the mass percentage A1 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B1 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5, wherein the peripheral region of the carbon-silicon composite material is a region extending from the outer surface of the carbon-silicon composite material to the interior of the carbon-silicon composite material within a distance of r / 2, and r represents the short diameter of the carbon-silicon composite material.
[0017] During the cycling of a secondary battery, silicon nanoparticles may expand in volume. When the peripheral region of the carbon-silicon composite material satisfies 0.8≤B1 / A1≤2.5, the silicon nanoparticles can be more evenly attached to the carbon skeleton. The carbon matrix particles can significantly limit the volume expansion of the silicon nanoparticles. At the same time, the pores formed during the deposition of the silicon nanoparticles also provide a buffer space for the expansion of the silicon itself, thereby improving the structural stability of the negative electrode active material and the cycling performance of the secondary battery.
[0018] In any embodiment, in the central region of the carbon-silicon composite material, the mass percentage A2 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B2 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 1.05≤A2 / B2≤50, optionally, 1.05≤A2 / B2≤3, wherein the central region of the carbon-silicon composite material is a region within r / 2 of the geometric center of the carbon-silicon composite material.
[0019] The central area of the carbon-silicon composite material of the present application satisfies 1.05≤A2 / B2≤50, which can further improve the uniformity of the attachment of silicon nanoparticles to the carbon skeleton, thereby further improving the structural stability of the negative electrode active material and improving its cycle performance.
[0020] In any embodiment, the mass percentage A of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has a decreasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material, and the mass percentage B of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has an increasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material.
[0021] The carbon content of the carbon-silicon composite material of the present application increases from the peripheral region to the central region, which can better support the three-dimensional network cross-linked pore structure and improve the structural stability of the carbon skeleton. The silicon content of the carbon-silicon composite material of the present application increases from the central region to the peripheral region, which can significantly increase the capacity of the negative electrode active material. The distribution of carbon and silicon elements in the carbon-silicon composite material of the present application effectively improves the cycle stability of the battery.
[0022] In any embodiment, the mass percentage of the silicon nanoparticles in the carbon-silicon composite material is greater than or equal to 40%; optionally, it is 40%-60%.
[0023] Traditional carbon-silicon composites struggle to effectively increase silicon loading due to the easy aggregation of nanoparticles, preventing them from effectively increasing their capacity and, consequently, optimizing the battery's energy density. This application, by attaching silicon nanoparticles to carbon-based particles with a carbon skeleton, effectively increases the silicon content in the carbon-silicon composite, improving its theoretical capacity and reducing its use in the negative electrode film layer, thereby reducing negative electrode expansion and achieving simultaneous optimization of the secondary battery's energy density and cycle performance.
[0024] In any embodiment, the negative electrode active material further comprises a carbon-based active material.
[0025] In any embodiment, the carbon-based active material includes one or more of graphite, hard carbon, soft carbon, and porous carbon.
[0026] Adding carbon-based active materials to negative electrode active materials can improve the rate performance and cycle performance of secondary batteries.
[0027] In any embodiment, based on the total mass of the negative electrode active material, the mass percentage α of the carbon-silicon composite material is 10%-100%. Optionally, the mass percentage α of the carbon-silicon composite material is 30%-40%.
[0028] When the carbon-silicon composite material content of the present application is 10%-100%, the secondary battery has a high energy density. When the mass percentage of the carbon-silicon composite material is 30%-40%, the battery has improved cycle performance and rate performance while increasing energy density.
[0029] In any embodiment, the negative electrode film layer includes a conductive agent, the conductive agent includes carbon nanotubes, the aspect ratio of the carbon nanotubes is greater than 2500, and / or,
[0030] Based on the total mass of the negative electrode film layer, the mass percentage of the carbon nanotubes is 0.1% to 0.5%, and can be optionally 0.3% to 0.5%.
[0031] Due to the high content of carbon-silicon composite materials in this application, the volume expansion of silicon nanoparticles will cause the negative electrode film layer to rebound to a certain extent. After repeated charge and discharge, the particles in the negative electrode active material will lose electrical contact. The use of carbon nanotubes with the above aspect ratio can suppress the rebound of the negative electrode film layer and enhance the conductivity of the negative electrode sheet. Moreover, in order to improve the mass energy density of the battery, the battery adopts a thick coating design. The addition of carbon nanotubes improves the electron transport of the thick electrode sheet through long-range conductivity, further optimizing the battery's rate performance.
[0032] In any embodiment, the negative electrode plate satisfies:
[0033] The unit area density of the negative electrode film layer on one side of the negative electrode plate is 4 mg / cm 2 -15mg / cm 2 , optional 8mg / cm 2 -14mg / cm 2 , and / or,
[0034] The compaction density of the negative electrode film layer on one side of the negative electrode plate is 1.6 g / cm 3 -1.8g / cm 3 .
[0035] The battery adopts a thick coating design to ensure the loading of active materials and further improve the battery's mass energy density. The electrode has a high surface density and the pole piece has an appropriate compaction density, which can ensure the mass energy density of the secondary battery while taking into account the battery's rate performance.
[0036] In any embodiment, the positive electrode active material includes Li a Ni x Co y M 1-x-y O 2-b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2; -0.2≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.08.
[0037] Increasing the content of transition metal nickel in the positive electrode active material can improve the mass energy density of the secondary battery.
[0038] In any embodiment, the positive electrode plate satisfies:
[0039] The unit area density of the positive electrode film layer on one side of the positive electrode sheet is 18 mg / cm 2 -45mg / cm 2 , optional 25mg / cm 2 -45mg / cm 2 and / or,
[0040] The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 3.3 g / cm 3 -3.6g / cm 3 , optional 3.4g / cm 3 -3.6g / cm 3 .
[0041] The positive electrode film layer's unit area density and compaction density within the above ranges can ensure that the secondary battery has a high mass energy density while further improving the secondary battery's rate performance and cycle performance. Specifically, when the positive electrode film layer's unit area density and compaction density are low, the positive electrode film layer contains less positive electrode active material per unit area, resulting in a lower mass energy density of the secondary battery. When the positive electrode film layer's unit area density and compaction density are too high, the positive electrode film layer contains more positive electrode active material per unit area, resulting in excessive transition metal dissolution and deposition at the negative electrode, which affects the secondary battery's cycle performance.
[0042] In any embodiment, the mass energy density of the secondary battery is 280Wh / kg-500Wh / kg, optionally 360Wh / kg-500Wh / kg or 400Wh / kg-500Wh / kg; and / or,
[0043] C0 is the capacity of the secondary battery, in Ah. C0 is 35Ah-200Ah, and can be optionally 45Ah-190Ah.
[0044] A second aspect of the present application provides an electrical device comprising the secondary battery described in the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] FIG1 is a schematic diagram of a secondary battery cell according to an embodiment of the present application;
[0046] FIG2 is an exploded view of a secondary battery cell according to an embodiment of the present application shown in FIG1 ;
[0047] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0048] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0049] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0050] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0051] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery cell; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0052] Below, the embodiments of the battery and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0053] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0056] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0057] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0058] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0059] High-energy lithium-ion batteries are gaining widespread market attention due to their crucial role in strategically important areas such as advanced information processing devices and electric vehicles. Although the mass energy density of commercially available lithium-ion batteries has reached 150-200 Wh / kg, further increases in mass energy density to meet market demand are difficult due to the theoretical capacity limitations of the positive and negative electrode materials.
[0060] [Secondary battery]
[0061] Based on this, the present application proposes a secondary battery to further improve the mass energy density of the secondary battery.
[0062] In some embodiments, a secondary battery includes: a positive electrode sheet and a negative electrode sheet, the positive electrode sheet including a positive electrode film layer, the positive electrode film layer including a positive electrode active material including a transition metal element, the molar content of nickel being not less than 85% based on the total molar number of the transition metal elements in the positive electrode active material, and the energy per unit area of the positive electrode film layer on a single side of the positive electrode sheet being 15-35 mWh / cm2, optionally 20-35 mWh / cm2;
[0063] The negative electrode plate includes a negative electrode film layer, which includes a negative electrode active material of a carbon-silicon composite material. The carbon-silicon composite material includes carbon matrix particles with a carbon skeleton and silicon nanoparticles attached to the carbon skeleton.
[0064] In some embodiments, the carbon skeleton is a solid structure, and the silicon nanoparticles are attached to at least a portion of the surface of the carbon skeleton.
[0065] In some embodiments, the carbon skeleton is a porous skeleton structure, and the silicon nanoparticles are attached to at least a portion of the surface of the carbon skeleton and the pores of the carbon skeleton. The silicon nanoparticles can fill all or part of the pores of the carbon skeleton.
[0066] In some embodiments, the carbon skeleton is a porous skeleton structure, wherein the pores represent a recessed structure that is recessed relative to the outer surface of the negative electrode active material and is recessed into the interior of the negative electrode active material, or a through-hole that penetrates the negative electrode active material. The composition of the pore structure includes pore size, pore length, pore size distribution, etc. The pore size of the porous carbon skeleton of the carbon matrix particles includes micropores, mesopores, and macropores. Micropores refer to pores with a diameter of less than about 2 nanometers. Mesopores refer to pores with a diameter of about 2 nanometers to about 5 nanometers. Macropores refer to pores with a diameter greater than 50 nanometers.
[0067] The characteristics of the positive electrode sheet and the negative electrode sheet can be observed and tested under a scanning electron microscope and / or an energy spectrometer after disassembling the battery. As an example, the carbon skeleton of the carbon-silicon composite material can be tested using equipment and methods known in the art. For example, it can be tested using a scanning electron microscope (ZEISS Sigma 300). As an example, the following steps can be followed: after disassembling the battery, take the negative electrode sheet, cut the negative electrode sheet into a sample to be tested of a certain size (for example, 6mm×6mm), clamp the sample to be tested with two conductive and thermally conductive thin sheets (such as copper foil), stick the sample to be tested and the copper foil with glue (such as double-sided tape), press it with a flat iron block of a certain mass (such as 400g) for a certain time (such as 1h), trim the edges with scissors, and stick it on a sample table with conductive glue. Then, the sample stage is placed on the sample holder and fixed. The argon ion cross-section polisher (such as IB-19500CP) is powered on and vacuumed (for example, 10Pa-4Pa). The argon flow rate (for example, 0.15MPa) and voltage (for example, 8KV) and polishing time (for example, 2 hours) are set. The sample stage is adjusted to the rocking mode and polishing is started. After polishing, a scanning electron microscope (for example, ZEISS Sigma 300) is used to obtain an ion polished cross-sectional morphology image of the sample to be tested. The collected scanning electron microscope images are analyzed using an energy spectrometer to obtain the distribution statistics of carbon and silicon elements. Similarly, the positive electrode piece is scanned and elementally analyzed to analyze its composition.
[0068] In some embodiments, the particle size of the silicon nanoparticles is at the nanometer level, and when the silicon nanoparticles are deposited in the pore structure, the silicon nanoparticles are more easily and evenly attached to the carbon skeleton.
[0069] In some embodiments, carbon matrix particles and silicon nanoparticles are combined to form a carbon-silicon composite material. The carbon-silicon composite material may be particles with irregular geometric shapes. In this case, the three-axis diameter characterization method can be used to characterize its particle diameter. The specific characterization method is as follows: the major diameter l and the minor diameter r are measured on the plane projection of the carbon-silicon composite material, and the thickness h of the carbon-silicon composite material is measured in the direction perpendicular to the projection plane; it can also be understood as placing the carbon-silicon composite material in a rectangular parallelepiped tangent to it, with the long side of the rectangular parallelepiped being l, the short side being r, and the thickness being h, so as to reflect the actual size of the carbon-silicon composite material.
[0070] In some embodiments, the energy per unit area of the positive electrode film layer on one side of the positive electrode sheet can be 15mWh / cm 2 、16mWh / cm 2 、17mWh / cm 2 、18mWh / cm 2 、19mWh / cm 2 、20mWh / cm 2 、21mWh / cm 2 、22mWh / cm 2 、23mWh / cm 2 , 25mWh / cm 2 、27mWh / cm 2 、29mWh / cm 2 、31mWh / cm 2 、33mWh / cm 2 、35mWh / cm 2 Or a value in the range formed by any two of the above points.
[0071] The unit area energy of the positive electrode film layer on one side of the positive electrode plate can be measured using methods and equipment commonly used in the art. As an example, the unit area energy of the positive electrode film layer on one side of the positive electrode plate can be measured according to the following steps: the battery cell is left at a certain temperature (e.g., 25°C) for a certain time (e.g., 2 hours), ensuring that the temperature of the battery cell is room temperature (e.g., 25°C). After charging the battery cell at a certain rate (e.g., 0.33C) to the charge cut-off voltage at a certain temperature (e.g., 25°C), continue to charge the battery cell at a constant voltage at the charge cut-off voltage until the current reaches 0.05C and the charge is cut off (C represents the rated capacity of the battery cell). After the battery cell is left at a certain temperature (e.g., 25°C) for a certain time (e.g., 1 hour), it is discharged at a certain rate (0.33C) to the discharge cut-off voltage at a certain temperature (e.g., 25°C), and the total discharge energy is recorded as E0. Disassemble the battery, remove the positive electrode plate, and use a ruler to measure the length and width of the film on the positive electrode plate to obtain the area value S0 of the positive electrode film. When the positive electrode sheet is coated on both sides, the energy per unit area of the positive electrode film layer = E0 / (2×S0); when the positive electrode film layer is coated on one side, the energy per unit area of the positive electrode sheet = E0 / S0.
[0072] In the above test method, the charge cut-off voltage is 4.25V, the discharge cut-off voltage is 2.0V, and the charge rate and discharge rate are both 0.33C.
[0073] The present application breaks through the limitation of the theoretical capacity of positive and negative electrode materials in the prior art by combining a positive electrode active material with a high nickel content with a carbon-silicon composite material, and realizes the preparation of a high energy density secondary battery.
[0074] The weight of the bare cell and the shell of the secondary battery can be tested using equipment and methods known in the art. For example, the test can be performed using an electronic balance. As an example, the following steps can be followed: first, separate the outer shell and the bare cell of the battery; second, to remove the electrolyte free inside the bare cell, the bare cell can be soaked in dimethyl carbonate (DMC) solvent for 4 hours, and then transferred to a 60°C forced air drying oven for 4 hours to obtain a dried bare cell; third, the outer shell and the bare cell of the battery are placed on an electronic balance for weighing to obtain the weight of the outer shell and the bare cell of the secondary battery.
[0075] The mass percentage of the carbon-silicon composite material can be measured using equipment and methods known in the art. For example, it can be obtained by measuring the mass of the negative electrode active material in the negative electrode film layer, the silicon content, and the silicon content in the carbon-silicon composite material and converting them.
[0076] As an example, you can follow the steps below:
[0077] (1) Take two batteries with exactly the same design, disassemble the first battery, and take out the negative electrode. Soak the negative electrode in dimethyl carbonate (DMC) solvent for 4 hours, then calcine it in a box-type resistance furnace at 400°C for 2 hours to remove the binder, and obtain the negative electrode active material and weigh it, which is recorded as M0. Digest the negative electrode active material sample with aqua regia and hydrofluoric acid, and perform ICP testing with the completely digested solution to obtain the mass percentage of silicon element in the negative electrode active material, which is recorded as X0. The mass M1 of silicon in the negative electrode active material can be obtained by multiplying M0 and X0;
[0078] (2) Disassemble the other battery and remove the negative electrode. Soak the negative electrode in dimethyl carbonate (DMC) solvent for 4 hours, then calcine it in a box-type resistance furnace at 400°C for 2 hours to remove the binder and other auxiliary materials in the electrode to obtain the negative electrode active material, and use graded screening or other screening methods known in the art to separate the carbon-silicon composite material. Then, use aqua regia and hydrofluoric acid to completely digest the separated carbon-silicon composite material, and perform ICP testing on the decomposed solution to obtain the mass content ratio of silicon element in the carbon-silicon composite material (X1);
[0079] (3) According to the above calculation results, it can be obtained that the mass of the carbon-silicon composite material in the secondary battery cell is M2=M1 / X1, and the mass percentage of the carbon-silicon composite material is M2 / M0×100%.
[0080] [Negative electrode active material]
[0081] In some embodiments, the base particle includes a three-dimensional network cross-linked pore structure, and at least a portion of the silicon nanoparticles are disposed in the three-dimensional network cross-linked pore structure.
[0082] In the present application, the “three-dimensional network cross-linked pore structure” refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in the pore structure formed by carbon matrix particles.
[0083] Although silicon nanoparticles have a large theoretical gram capacity, they expand significantly during charge and discharge, resulting in poor structural stability and deteriorating battery cycle performance. The carbon-based particles in this application possess a stable, three-dimensional, cross-linked porous skeleton structure, which provides ample space for the silicon nanoparticles, making them less likely to agglomerate while mitigating the adverse effects of their volume expansion on the negative electrode, thereby effectively improving the cycle performance of secondary batteries.
[0084] A high nickel content can increase the gram capacity of the positive electrode, thereby increasing the mass energy density of the secondary battery. However, an excessively high nickel content can increase the lithium-nickel mixing phenomenon, making it easy for transition metals to dissolve and deposit on the negative electrode, affecting the battery's cycle performance. The three-dimensional cross-linked carbon skeleton of the carbon-silicon material of the present application can form a complex with the positive electrode active material, reducing the deposition of transition metals on silicon nanoparticles and reducing the negative impact of the deposition of transition metals on the negative electrode on the performance of silicon-based materials, thereby further improving the cycle performance of the secondary battery.
[0085] In some embodiments, in the peripheral region of the carbon-silicon composite material, the mass percentage A1 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B1 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5, wherein the peripheral region of the carbon-silicon composite material is a region extending from the outer surface of the carbon-silicon composite material to the interior of the carbon-silicon composite material within a distance of r / 2, and r represents the short diameter of the carbon-silicon composite material.
[0086] The carbon-silicon composite material of the present application includes a peripheral region, which can be understood as a region extending from the outer surface of the carbon-silicon composite material to the interior of the carbon-silicon composite material within a distance of r / 2.
[0087] In some embodiments, B1 / A1 can be 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, or a range consisting of any two of the above values.
[0088] During the cycling of a secondary battery, silicon nanoparticles may expand in volume. When the peripheral region of the carbon-silicon composite material satisfies 0.8≤B1 / A1≤2.5, the silicon nanoparticles can be more evenly attached to the carbon skeleton. The carbon matrix particles can significantly limit the volume expansion of the silicon nanoparticles. At the same time, the pores formed during the deposition of the silicon nanoparticles also provide a buffer space for the expansion of the silicon itself, thereby improving the structural stability of the negative electrode active material and the cycling performance of the secondary battery.
[0089] In some embodiments, in the central region of the carbon-silicon composite material, the mass percentage A2 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B2 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 1.05≤A2 / B2≤50, optionally, 1.05≤A2 / B2≤3, wherein the central region of the carbon-silicon composite material is a region within r / 2 of the geometric center of the carbon-silicon composite material.
[0090] The carbon-silicon composite material of the present application includes a central region, which can be understood as a region within a distance r / 2 from the geometric center of the carbon-silicon composite body.
[0091] In some embodiments, A2 / B2 can be 1.05, 1.1, 1.15, 1.20, 1.25, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.0, 2.2, 2.5, 2.8, 3.0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, or a range consisting of any two of the above values.
[0092] The mass percentage of silicon and carbon in a carbon-silicon composite material relative to the total mass of the carbon-silicon composite material can be measured by methods and equipment known in the art. For example, the mass percentage of silicon can be measured by emission spectroscopy. As an example, the following steps can be followed: after disassembling the battery, take the negative electrode, remove the binder, take the carbon-silicon composite material as a sample, digest the sample with a strong acid solution (such as aqua regia and hydrofluoric acid HF), take the solution digested for 15 minutes and the solution completely digested for ICP testing, the silicon content in the solution digested for 15 minutes is the silicon content in the "peripheral area of the carbon-silicon composite material", and the difference in silicon content between the solution digested for completely and the solution digested for 15 minutes is the silicon content in the "central area of the carbon-silicon composite material". For example, the mass percentage of carbon can be measured by infrared absorption carbon-sulfur content analysis according to the GB / T20123-2006 test standard. As an example, the following steps can be followed: after disassembling the battery, take the negative electrode plate, remove the binder, and take the carbon-silicon composite material as a sample. The carbon content at 20 minutes of testing is the carbon content in the "peripheral area of the carbon-silicon composite body", and the difference between the carbon content at 20 minutes of testing and at the end of the test is the carbon content in the "central area of the carbon-silicon composite material".
[0093] The central area of the carbon-silicon composite material of the present application satisfies 1.05≤A2 / B2≤50, which can further improve the uniformity of the attachment of silicon nanoparticles to the carbon skeleton, thereby further improving the structural stability of the negative electrode active material, and can improve the mass energy density of the secondary battery while taking into account the long cycle performance.
[0094] In some embodiments, the mass percentage A of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has a decreasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material, and the mass percentage B of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has an increasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material.
[0095] In some embodiments, since the carbon-silicon composite material may be an irregular shape, the geometric center of the carbon-silicon composite material may be equal to the geometric center of a rectangular parallelepiped tangent to the carbon-silicon composite material.
[0096] The carbon content of the carbon-silicon composite material of the present application increases from the peripheral region to the central region, which can better support the three-dimensional network cross-linked pore structure and improve the structural stability of the carbon skeleton. The silicon content of the carbon-silicon composite material of the present application increases from the central region to the peripheral region, which can significantly increase the capacity of the negative electrode active material. The distribution of carbon and silicon elements in the carbon-silicon composite material of the present application effectively improves the cycle stability of the battery.
[0097] In some embodiments, the mass percentage of silicon nanoparticles in the carbon-silicon composite material is greater than or equal to 40%; optionally, 40%-60%.
[0098] In some embodiments, the mass percentage of the nanoparticles in the carbon-silicon composite material may be 40%, 45%, 50%, 60%, 75%, 80%, or a value within a range consisting of any two of the above values.
[0099] Traditional carbon-silicon composites struggle to effectively increase silicon loading due to the easy aggregation of nanoparticles, making it difficult to effectively improve the capacity of the carbon-silicon composite and, consequently, optimize the mass energy density of the battery. This application, by attaching silicon nanoparticles to carbon matrix particles with a carbon skeleton, effectively increases the silicon content in the carbon-silicon composite, improving the theoretical capacity of the carbon-silicon composite and reducing its usage in the negative electrode film layer, thereby reducing negative electrode expansion and achieving simultaneous optimization of the secondary battery's energy density and cycle performance.
[0100] In some embodiments, the negative electrode active material further includes a carbon-based active material.
[0101] In some embodiments, the carbon-based active material includes one or more of graphite, hard carbon, soft carbon, and porous carbon.
[0102] In some embodiments, the carbon-based active material is selected from graphite or hard carbon. In some embodiments, the carbon-based active material is selected from graphite.
[0103] Adding carbon-based active materials to negative electrode active materials can improve the rate performance and cycle performance of secondary batteries.
[0104] In some embodiments, based on the total mass of the negative electrode active material, the mass percentage α of the carbon-silicon composite material is 10%-100%.
[0105] Optionally, the mass percentage of the carbon-silicon composite material is 30%-40%.
[0106] In some embodiments, based on the total mass of the negative electrode active material, the mass percentage α of the carbon-silicon composite material can be 10%, 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or a value in the range consisting of any two of the above points.
[0107] When the carbon-silicon composite material content of the present application is 10%-100%, the secondary battery has a high energy density. When the mass percentage of the carbon-silicon composite material is 30%-40%, the battery has improved cycle performance and rate performance while increasing energy density.
[0108] In some embodiments, the negative electrode film layer includes a conductive agent, the conductive agent includes carbon nanotubes, the aspect ratio of the carbon nanotubes is greater than 2500, and / or,
[0109] Based on the total mass of the negative electrode film layer, the mass percentage of the carbon nanotubes is 0.1% to 0.5%, and can be optionally 0.3% to 0.5%.
[0110] In some embodiments, the mass percentage of carbon nanotubes may be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or a value within the range formed by any two of the foregoing.
[0111] In some embodiments, the conductive agent may further include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, graphene, and carbon nanofibers.
[0112] Due to the high content of carbon-silicon composite materials in this application, the volume expansion of silicon nanoparticles will cause the negative electrode film layer to rebound to a certain extent. After repeated charge and discharge, the particles in the negative electrode active material will lose electrical contact. The use of carbon nanotubes with the above aspect ratio can suppress the rebound of the negative electrode film layer and enhance the conductivity of the negative electrode sheet. Moreover, in order to improve the mass energy density of the battery, the battery adopts a thick coating design. The addition of carbon nanotubes improves the electron transport of the thick electrode sheet through long-range conductivity, further optimizing the dynamic performance of the battery.
[0113] In some embodiments, the negative electrode sheet satisfies the following requirements: the unit area density of the negative electrode film layer on one side of the negative electrode sheet is 4 mg / cm 2 -15mg / cm 2 , optional 8mg / cm 2 -14mg / cm 2 , and / or,
[0114] The compaction density of the negative electrode film layer on one side of the negative electrode sheet is 1.6g / cm 3 -1.8g / cm 3 .
[0115] In some embodiments, the unit area density of the negative electrode film layer on one side of the negative electrode sheet can be 4 mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 , 14mg / cm 2 、15mg / cm 2 Or a value in the range formed by any two of the above points.
[0116] In some embodiments, the compaction density of the negative electrode film layer on one side of the negative electrode sheet can be 1.6 g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 Or a value in the range formed by any two of the above points.
[0117] The battery adopts a thick coating design to ensure the loading of active materials, further improving the battery's mass energy density and the energy per unit area of the positive electrode film. Furthermore, while the electrode has a high surface density, the pole piece has an appropriate compaction density, which can ensure the mass energy density of the secondary battery while taking into account the battery's dynamic performance.
[0118] [Negative electrode]
[0119] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes the negative electrode active material of the present application.
[0120] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0121] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0122] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0123] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0124] [Positive electrode active material]
[0125] In some embodiments, the positive electrode active material includes Li a Ni x Co y M 1-x-y O 2-b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2; -0.2≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.08.
[0126] In some embodiments, a may be 0.2, 0.4, 0.6, 0.8, 1.0, 1.2, or a value in the range formed by any two of the foregoing values.
[0127] In some embodiments, b may be -0.2, -0.1, 0, 0.1, 0.2, or a value in the range formed by any two of the foregoing values.
[0128] In some embodiments, x may be 0.85, 0.87, 0.89, 0.91, 0.93, 0.95, 0.97, or a value in the range formed by any two of the foregoing points, and y may be 0, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, or a value in the range formed by any two of the foregoing points.
[0129] Increasing the content of transition metal nickel in the positive electrode active material can improve the mass energy density of the secondary battery.
[0130] In some embodiments, M comprises Mn. In some embodiments, M comprises Al. In some embodiments, M comprises B. In some embodiments, M comprises Zr. In some embodiments, M comprises Sr. In some embodiments, M comprises W. In some embodiments, M comprises Mg. In some embodiments, M comprises Nb.
[0131] Ternary cathode active materials have superior electrochemical performance compared to commonly used binary cathode active materials. Specifically, doping the cathode active material with the aforementioned M element can optimize particle size and distribution, improving the transport properties of electrons and lithium ions within the cathode active material, thereby increasing the mass energy density of the secondary battery.
[0132] In some embodiments, the positive electrode sheet satisfies:
[0133] The unit area density of the positive electrode film layer on one side of the positive electrode sheet is 19 mg / cm 2 -45mg / cm 2 , optional 25mg / cm 2 -45mg / cm 2 and / or,
[0134] The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 3.3g / cm 3 -3.6g / cm 3 , optional 3.4g / cm 3 -3.6g / cm 3 .
[0135] In some embodiments, the unit area density of the positive electrode film layer on one side of the positive electrode sheet can be 19 mg / cm 2 , 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 , 26mg / cm 2 , 28mg / cm 2 、30mg / cm 2 、32mg / cm 2 、34mg / cm 2 、36mg / cm 2 、38mg / cm 2 , 40mg / cm 2 , 42mg / cm 2 , 44mg / cm 2 Or a value in the range formed by any two of the above points.
[0136] In some embodiments, the compaction density of the positive electrode film layer on one side of the positive electrode sheet can be 3.45 g / cm 3 , 3.5g / cm 3 、3.55g / cm 3 Or a value in the range formed by any two of the above points.
[0137] The unit area density and compaction density of the positive electrode film layer on one side of the positive electrode plate or the negative electrode film layer on one side of the negative electrode plate can be measured using methods and equipment commonly used in the field. As an example, the compaction density of the film layer on one side of the electrode plate can be operated according to the following steps: when the electrode plate is coated on one side, the compaction density of the film layer on one side of the electrode plate = m / (V1-V2); when the electrode plate is coated on both sides, the compaction density of the film layer on one side of the electrode plate = m / [2×(V1-V2)], where m represents the weight of the film layer, V1 represents the volume of the electrode plate, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the electrode plate. The product of the surface area of the electrode plate and the thickness of the electrode plate is the volume V1 of the electrode plate, and the product of the surface area of the electrode plate and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the electrode plate are obtained by measuring the thickness of the empty foil in the tab area with a micrometer. As an example, the unit area density of the film layer on one side of the electrode can be calculated as follows: When the electrode is coated on one side, the unit area density of the film layer on one side of the electrode = m / S. When the electrode is coated on both sides, the unit area density of the film layer on one side of the electrode = m / (2×S), where m represents the weight of the film layer. S represents the area of the film layer. m can be calculated by subtracting the weight of the current collector from the weight of the electrode. The length and width of the film layer can be measured using a ruler.
[0138] The positive electrode film layer's unit area density and compaction density within the above ranges can ensure that the secondary battery has a high mass energy density and a high energy per unit area of the positive electrode film layer, while also further improving the secondary battery's power performance and cycle performance. Specifically, when the positive electrode film layer's unit area density and compaction density are low, the positive electrode film layer contains less positive electrode active material per unit area, resulting in a lower mass energy density of the secondary battery. When the positive electrode film layer's unit area density and compaction density are too high, the positive electrode film layer contains more positive electrode active material per unit area, resulting in excessive amounts of transition metal dissolved and deposited at the negative electrode, which affects the secondary battery's cycle performance.
[0139] [Positive electrode]
[0140] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the present application.
[0141] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0142] In some embodiments of the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0143] In some embodiments of the present application, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0144] In some embodiments of the present disclosure, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0145] In some embodiments of the present disclosure, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0146] [Electrolytes]
[0147] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0148] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0149] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0150] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0151] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0152] [Isolation film]
[0153] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0154] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0155] [Preparation method]
[0156] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0157] In some embodiments, the mass energy density of the secondary battery is 280Wh / kg-500Wh / kg, optionally 360Wh / kg-500Wh / kg or 400Wh / kg-500Wh / kg; and / or,
[0158] The capacity C0 of the secondary battery is 35Ah-200Ah, and can be optionally 45Ah-190Ah.
[0159] In some embodiments, the mass energy density of the secondary battery can be 280Wh / kg, 300Wh / kg, 320Wh / kg, 350Wh / kg, 360Wh / kg, 370Wh / kg, 380Wh / kg, 390Wh / kg, 400Wh / kg, 410Wh / kg, 420Wh / kg, 430Wh / kg, 450Wh / kg, 500Wh / kg, 360Wh / kg, 360Wh / kg or a value in the range formed by any two of the above points.
[0160] In some embodiments, the capacity C0 of the secondary battery is 35 Ah, 40 Ah, 43 Ah, 45 Ah, 48 Ah, 50 Ah, 60 Ah, 80 Ah, 100 Ah, 130 Ah, 160 Ah, 200 Ah, or a value in a range formed by any two of the foregoing values.
[0161] In the present application, the mass energy density of a secondary battery can be measured using methods and equipment commonly used in the art. As an example, the mass energy density of a secondary battery can be measured according to the following steps: let the battery cell stand at a certain temperature (e.g., 25°C) for a certain time (e.g., 2h), and ensure that the temperature of the battery cell is room temperature (e.g., 25°C). After charging the battery cell to the charge cut-off voltage at a certain rate (e.g., 0.33C) at a certain temperature (e.g., 25°C), continue to charge at a constant voltage at the charge cut-off voltage until the current is 0.05C and the charge is cut off (C represents the rated capacity of the battery cell). After the battery cell is allowed to stand at a certain temperature (e.g., 25°C) for a certain time (e.g., 1h), discharge the battery cell to the discharge cut-off voltage at a certain rate (0.33C) at a certain temperature (e.g., 25°C), and record the total discharge energy of the battery cell as E0. Place the battery cell on an electronic balance until the weight is stable, and read the battery cell weight value M0. Battery mass energy density = battery cell discharge energy E0 / battery cell weight M0.
[0162] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0163] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.
[0164] In some embodiments of the present invention, referring to Figure 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0165] In some embodiments, the shell weight z of the secondary battery and the bare cell weight JR of the secondary battery satisfy the following relationship: 0.01≤z / JR≤0.42; optionally 0.01≤z / JR≤0.1 or 0.02≤z / JR≤0.07.
[0166] In some embodiments, z / JR may be 0.015, 0.025, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, or a value in a range consisting of any two of the foregoing values.
[0167] In some embodiments, the secondary battery is a soft-pack battery cell, and z / JR is 0.01-0.1 or 0.03-0.07.
[0168] In some embodiments, the secondary battery is a hard-shell battery cell, and z / JR is 0.1-0.42 or 0.1-0.3.
[0169] Through the above structural design, it can be ensured that the mass energy density of the secondary battery is significantly higher, while the outer wall has sufficient structural strength, and the secondary battery has higher safety performance.
[0170] [Battery Module]
[0171] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain one or more battery cells. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.
[0172] FIG3 shows an example battery module 4. Referring to FIG3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 5 may be secured together using fasteners.
[0173] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0174] [Battery Pack]
[0175] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0176] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0177] [Electrical devices]
[0178] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect.
[0179] Electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0180] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0181] Figure 6 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0182] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0183] Example
[0184] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0185] Example 1
[0186] 1. Preparation method
[0187] 1. Preparation of positive electrode sheet
[0188] Preparation of the positive electrode active material: Lithium hydroxide and a dried high-nickel ternary precursor were weighed according to the stoichiometric ratio of the chemical formula. The mixture was mixed thoroughly in a high-speed mixer and then sintered in a kiln at 760°C for 20 hours in an oxygen atmosphere. After cooling, the matrix material was obtained. This material was washed with water at a mass ratio of 1:5 for 30 minutes, centrifuged, filtered, and then vibrated and dried at a vibration frequency of 30 Hz for 5 hours to obtain the positive electrode active material.
[0189] The positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are mixed evenly in an N-methylpyrrolidone (NMP) solution at a mass ratio of 97%: 1%: 2% to prepare a positive electrode slurry, which is then evenly coated on the positive electrode current collector, applied to the surface of aluminum foil using an extrusion coater and dried, and then cold-pressed by a cold press to prepare the final positive electrode sheet.
[0190] 2. Preparation of negative electrode sheet
[0191] Preparation of carbon-silicon composites: Through chemical vapor deposition, a silicon precursor is transformed into silicon nanoparticles attached to a porous carbon framework, resulting in a carbon-silicon composite. By adjusting deposition conditions such as gas flow and reaction chamber pressure, the size of the silicon nanoparticles and their deposition depth within the porous carbon material can be controlled.
[0192] The negative electrode active materials, artificial graphite and carbon-silicon composite materials, conductive agent carbon black, carbon nanotubes, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a certain proportion in an appropriate amount of deionized water to form a uniform negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector, and after drying and other processes, a negative electrode film layer is obtained. The aspect ratio of the carbon nanotubes is 3000, and the mass percentage of the carbon nanotubes based on the total mass of the negative electrode film layer is 0.4%.
[0193] 3. Isolation film
[0194] Polyethylene film (PE film) is used as the separator.
[0195] 4. Electrolyte
[0196] Ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0197] 5. Preparation of batteries
[0198] The positive electrode sheet, separator, and negative electrode sheet are wound in sequence to obtain a bare cell. The bare cell is placed in a soft-pack packaging shell, dried, and then injected with electrolyte. After vacuum packaging, standing, forming, shaping, and other processes, a lithium-ion battery is obtained.
[0199] Examples 2-4
[0200] The preparation method is similar to that of Example 1, except that: Examples 2-3 adjusted the design parameters of the shell, and Example 4 used a hard shell packaging shell and adjusted the shell design parameters at the same time. The specific parameters are detailed in Table 1.
[0201] Example 5-20
[0202] The preparation method is similar to that of Example 1, except that the relevant parameters in the preparation steps of the negative electrode active material or the positive electrode active material are adjusted. The specific parameters are shown in Table 1.
[0203] Comparative Examples 1-4
[0204] The preparation method is similar to that of Example 1, except that the type of negative electrode active material added or the relevant parameters in the preparation steps of the positive electrode active material or the negative electrode active material are adjusted. Comparative Example 1 uses a hard shell packaging case, as shown in Table 1 for details.
[0205] 2. Performance Testing
[0206] 1. Battery performance test
[0207] 1.1 Mass energy density
[0208] 1) The discharge energy measurement method of a battery cell is as follows:
[0209] Allow the battery cell to rest at 25°C for 2 hours, ensuring the temperature of the battery cell is 25°C. Charge the battery cell at 0.33C at 25°C to the charge cutoff voltage, then continue constant voltage charging at the charge cutoff voltage until the current reaches 0.05C, at which point the charge is cutoff (where C represents the rated capacity of the battery cell). Allow the battery cell to rest at 25°C for 1 hour, then discharge the battery cell at 0.33C at 25°C to the discharge cutoff voltage. Record the total discharge energy of the battery cell as E0. The charge cutoff voltage is 4.25V, and the discharge cutoff voltage is 2.0V.
[0210] 2) The battery cell weight measurement method is as follows:
[0211] Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0.
[0212] 3) The formula for calculating battery mass energy density is as follows:
[0213] Battery mass energy density = battery cell discharge energy E0 / battery cell weight M0
[0214] 1.2 Cycle performance
[0215] The voltage calibration method is as follows:
[0216] Allow the battery cell to rest at 25°C for 2 hours, ensuring the cell temperature is 25°C. Charge the battery cell to 4.25V at 0.33°C, charge it at a constant voltage of 4.25V to a current of 0.05°C, and allow it to rest for 1 hour. Discharge it at 0.33°C for 0.95°C at 25°C, recording the voltage V1 at this point. After resting for 5 minutes, discharge it at 0.33°C for 2.0V at 25°C. After resting for 5 minutes, charge the battery cell at 0.33°C for 0.97°C at 25°C, and after resting for 5 minutes, record the voltage V2 at this point.
[0217] The cycle test process is as follows:
[0218] Allow the battery cell to rest at 25°C for 2 hours to ensure the cell temperature is 25°C. Charge the battery cell to voltage V2 at 0.33°C at 25°C and allow it to rest for 0.5 hour. Discharge the battery cell to voltage V1 at 0.33°C at 25°C and allow it to rest for 0.5 hour. Perform a full charge-discharge cycle test until the secondary battery capacity decays to 80% of its initial capacity. Stop the test and record the number of cycles.
[0219] 1.3. Rate performance
[0220] At 25°C, fully charge the battery at x C and fully discharge it at 1 C 10 times. Then, fully charge the battery again at x C, remove the negative electrode, and observe lithium deposition on the surface. If no lithium deposition occurs, increase the charge rate x C by 0.1 C and repeat the test until lithium deposition occurs. The maximum charge rate of the battery is calculated by subtracting 0.1 C from the charge rate at this point. The full charge cutoff voltage is 4.25V, and the full discharge cutoff voltage is 2.0V.
[0221] 1.4 Capacity Test
[0222] Allow the battery cell to rest at 25°C for 2 hours, ensuring the temperature of the battery cell is 25°C. Charge the battery cell at 0.33C at 25°C to the charge cutoff voltage, then continue constant voltage charging at the charge cutoff voltage until the current reaches 0.05C, at which point the charge is cutoff (where C represents the rated capacity of the battery cell). Allow the battery cell to rest at 25°C for 1 hour, then discharge the battery cell at 0.33C at 25°C to the discharge cutoff voltage, and record the total discharge capacity (C0) of the battery cell. The charge cutoff voltage is 4.25V, and the discharge cutoff voltage is 2.0V.
[0223] 1.5. Battery case weight and bare cell weight
[0224] First, separate the outer shell of the battery and the bare cell; second, in order to remove the free electrolyte inside the bare cell, the bare cell can be soaked in dimethyl carbonate (DMC) solvent for 4 hours, and then transferred to a 60°C forced air drying oven for 4 hours to obtain a dried bare cell; third, place the outer shell of the battery and the bare cell on an electronic balance for weighing, respectively, to obtain the weight of the outer shell of the secondary battery (z) and the weight of the bare cell (JR).
[0225] 2. Positive electrode and negative electrode performance test
[0226] 2.1. Measurement method of unit area density of the positive electrode film layer on one side of the positive electrode sheet and the negative electrode film layer on one side of the negative electrode sheet
[0227] When the electrode is coated on one side, the unit area density of the film layer on one side of the electrode is m / S. When the electrode is coated on both sides, the unit area density of the film layer on one side of the electrode is m / (2×S), where m represents the weight of the film layer and S represents the area of the film layer. m can be obtained by subtracting the weight of the current collector from the weight of the electrode. The length and width of the film layer can be measured using a ruler.
[0228] 2.2. Test method for energy per unit area of the positive electrode film layer on one side of the positive electrode sheet
[0229] Allow the battery cell to rest at 25°C for 2 hours, ensuring the cell temperature is 25°C. Charge the cell at 0.33C at 25°C to the charge cutoff voltage, then continue constant voltage charging at this charge cutoff voltage until the current reaches 0.05C, at which point charging is terminated (where C represents the rated capacity of the cell). Allow the cell to rest at 25°C for 1 hour, then discharge it at 0.33C at 25°C to the discharge cutoff voltage. Record the total discharge capacity (C0) and the total discharge energy (E0) released by the cell. Disassemble the battery, remove the positive electrode, and use a ruler to measure the length and width of the film on the positive electrode to obtain the area value (S0) of the positive electrode film. When the positive electrode is coated on both sides, the energy per unit area of the positive electrode film = E0 / (2×S0); when the positive electrode is coated on one side, the energy per unit area of the positive electrode film = E0 / S0. The charge cutoff voltage is 4.25V, and the discharge cutoff voltage is 2.0V.
[0230] 2.3. Measurement method of silicon content in carbon-silicon composite materials
[0231] The silicon content was determined by emission spectroscopy (Inductively coupled plasma, ICP), as follows: A silicon-carbon composite material was digested with aqua regia and hydrofluoric acid HF. Since the digestion time is positively correlated with the depth of silicon dissolved in the silicon-carbon particles, gradient ICP tests were performed on solutions with different digestion times in this experiment. Combined with the statistical analysis results of transmission electron microscopy (TEM) of the silicon-carbon material, it was found that the silicon content in the solution digested for 15 minutes corresponded to the silicon content in the "peripheral area of the carbon-silicon composite material", and the difference in silicon content between the solution digested for complete digestion and that digested for 15 minutes corresponded to the silicon content in the "central area of the carbon-silicon complex".
[0232] 2.4. Measurement method of carbon content in carbon-silicon composite materials
[0233] The infrared absorption method for carbon-sulfur content analysis is conducted in accordance with the GB / T20123-2006 test standard, as follows: After disassembling the battery, take the negative electrode, remove the binder, and take the carbon-silicon composite material as a sample. The carbon content at 20 minutes of testing is the carbon content in the "peripheral area of the carbon-silicon composite", and the difference between the carbon content at 20 minutes of testing and at the end of the test is the carbon content in the "central area of the carbon-silicon composite material".
[0234] 2.5. Measurement method of short diameter r of carbon-silicon composite materials
[0235] The short diameter r is measured according to the three-axis characterization method, specifically as follows: the short diameter r is measured on a plane projection of the carbon-silicon composite.
[0236] 3. Analysis of test results of various embodiments and comparative examples
[0237] Batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The parameters of the secondary batteries are shown in Table 1 below, and the performance test results of the secondary batteries are shown in Table 2 below.
[0238] Table 1 Secondary battery parameters
[0239] Continuation Table 1
[0240] Continuation Table 1
[0241] Table 2. Test results of positive electrode and secondary battery performance
[0242] According to the results in the table above, from Comparative Example 1 and Examples 1-20, Comparative Example 2 and Example 1, and Examples 9-12, it can be seen that when the nickel content in the positive electrode active material is ≥85%, the resulting secondary battery has a higher mass energy density and the positive electrode film layer has a higher unit area energy. From Comparative Example 1 and Examples 1-20, it can be seen that when the negative electrode active material includes a carbon-silicon composite material with a three-dimensional network cross-linked pore structure, the resulting secondary battery has better cycle performance. From Comparative Example 3 and Example 1, and Comparative Example 4 and Example 5, it can be seen that carbon-silicon composite materials can improve the cycle performance of secondary batteries compared to other composite materials, such as silicon-oxygen materials.
[0243] As can be seen from Examples 1-4, using the same type of packaging shell, when the ratio of the shell weight to the bare cell weight decreases, the gravimetric energy density of the secondary battery increases. When the ratio of the secondary battery shell weight to the bare cell weight is controlled within the range of this application, the secondary battery has a higher gravimetric energy density.
[0244] As can be seen from Examples 1, 5, and 8, the mass percentage of the carbon-silicon composite material affects the mass energy density, cycle performance, and rate performance of the secondary battery. When the mass percentage of the carbon-silicon composite material is between 20% and 100%, the secondary battery has a good mass energy density. Furthermore, when the mass percentage of the carbon-silicon composite material is between 30% and 40%, a balance among mass energy density, cycle performance, and rate performance is achieved.
[0245] As can be seen from Examples 1 and 17-20, the ratio of silicon to carbon in the negative electrode active material affects the cycle performance and rate performance of the secondary battery. Specifically, when 0.8 ≤ B1 / A1 ≤ 2.5, especially 1 ≤ B1 / A1 ≤ 1.5, and 1.05 ≤ A2 / B2 ≤ 50, especially 1.05 ≤ A2 / B2 ≤ 3, the cycle performance and rate performance of the secondary battery can be improved.
[0246] As can be seen from Examples 1 and 13-16, increasing the membrane layer's areal density increases the secondary battery's mass energy density and the energy per unit area of the positive electrode membrane layer, but this can affect the secondary battery's cycle performance and rate capability to a certain extent. Within the range of the positive and negative electrode membrane layer's areal densities specified in this application, the resulting secondary battery exhibits a balance between mass energy density, energy per unit area of the positive electrode membrane layer, cycle performance, and rate capability.
[0247] In summary, the secondary battery of the present application achieves a higher mass energy density and improved cycle performance and rate performance through the close cooperation of the negative electrode active material and the positive electrode active material.
[0248] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery comprising: A positive electrode plate, the positive electrode plate comprising a positive electrode film layer, the positive electrode film layer comprising a positive electrode active material having a transition metal element, the molar content of nickel element being not less than 85% based on the total molar number of transition metal elements in the positive electrode active material, and the energy per unit area of the positive electrode film layer on a single side of the positive electrode plate being 15-35 mWh / cm 2 , optional 20-35mWh / cm 2 ; A negative electrode plate, the negative electrode plate comprises a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material of a carbon-silicon composite material, the carbon-silicon composite material comprises carbon matrix particles with a carbon skeleton and silicon nanoparticles attached to the carbon skeleton.
2. The secondary battery according to claim 1, characterized in that: The shell weight z of the secondary battery and the bare cell weight JR of the secondary battery satisfy the following relationship: 0.01≤z / JR≤0.42; optionally, 0.01≤z / JR≤0.1 or 0.02≤z / JR≤0.
07. 3 . The secondary battery according to claim 1 , wherein the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon nanoparticles are disposed in the three-dimensional network cross-linked pore structure.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: In the peripheral area of the carbon-silicon composite material, the mass percentage A1 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B1 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5, wherein the peripheral area of the carbon-silicon composite material is an area extending from the outer surface of the carbon-silicon composite material to the inside of the carbon-silicon composite material within a distance of r / 2, and r represents the short diameter of the carbon-silicon composite material.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: In the central area of the carbon-silicon composite material, the mass percentage A2 of the carbon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material and the mass percentage B2 of the silicon element of the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material satisfy 1.05≤A2 / B2≤50, optionally, 1.05≤A2 / B2≤3, wherein the central area of the carbon-silicon composite material is a region within r / 2 from the geometric center of the carbon-silicon composite material, and r represents the short diameter of the carbon-silicon composite material.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The mass percentage A of the carbon element in the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has a decreasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material, and the mass percentage B of the silicon element in the carbon-silicon composite material relative to the total mass of the carbon-silicon composite material has an increasing trend along the direction from the geometric center of the carbon-silicon composite material to the outer surface of the carbon-silicon composite material.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The mass percentage of the silicon nanoparticles in the carbon-silicon composite material is greater than or equal to 40%; it can be optionally 40%-60%.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The negative electrode active material also includes a carbon-based active material.
9. The secondary battery according to claim 8, characterized in that: The carbon-based active material includes one or more of graphite, hard carbon, soft carbon, and porous carbon.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: Based on the total mass of the negative electrode active material, the mass percentage α of the carbon-silicon composite material is 10%-100%. Optionally, the mass percentage of the carbon-silicon composite material is 30%-40%.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The negative electrode film layer includes a conductive agent, the conductive agent includes carbon nanotubes, the aspect ratio of the carbon nanotubes is greater than 2500, and / or, Based on the total mass of the negative electrode film layer, the mass percentage of the carbon nanotubes is 0.1% to 0.5%, and can be optionally 0.3% to 0.5%.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The negative electrode sheet satisfies: The unit area density of the negative electrode film layer on one side of the negative electrode plate is 4 mg / cm 2 -15mg / cm 2 , optional 8mg / cm 2 - 14mg / cm 2 , and / or, The compaction density of the negative electrode film layer on one side of the negative electrode plate is 1.6 g / cm 3 -1.8g / cm 3 .
13. The secondary battery according to any one of claims 1 to 12, wherein the positive electrode active material comprises Li a Ni x Co y M 1-x-y O 2- b , wherein M includes at least one of Mn, Al, B, Zr, Sr, Y, Sb, W, Ti, Mg and Nb, optionally, M includes at least one of Mn, Al, B, Zr, Sr, W, Mg and Nb; 0.2≤a≤1.2, 0.2≤b≤0.2; 0.85≤x≤1, 0≤y≤0.15, optionally, 0.92≤x≤0.98, 0<y≤0.
08.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The positive electrode sheet satisfies: The unit surface density of the positive electrode film layer on one side of the positive electrode sheet is 18 mg / cm 2 -45mg / cm 2 , optional 25mg / cm 2 -45mg / cm 2 and / or, The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 3.3 g / cm 3 -3.6g / cm 3 , optional 3.4g / cm 3 -3.6g / cm 3 .
15. The secondary battery according to any one of claims 1 to 14, characterized in that: The mass energy density of the secondary battery is 280Wh / kg-500Wh / kg, and can be 360Wh / kg-500Wh / kg or 400Wh / kg-500Wh / kg; and / or, The capacity C0 of the secondary battery is 35Ah-200Ah, and can be optionally 45Ah-190Ah.
16. An electrical device comprising the secondary battery according to any one of claims 1 to 15.
Citation Information
Patent Citations
Nanometer silicon composite negative electrode active material, preparation method, pole piece and lithium ion battery
CN115692638A
Apparatus for manufacturing negative electrode and method for manufacturing negative electrode
KR1020200132432A
